Integration of Effort: Securing Critical Infrastructure from Cyberattack. (17th April 2022) - Atkins, Sean; Lawson, Chappell
Abstract: Securing privately owned critical infrastructure from cyberattacks poses a novel challenge for the modern regulatory state. In this domain, the interests of the government are only partly aligned with those of nongovernmental owner‐operators, necessitating some sort of state action. However, because (1) security conditions change swiftly and (2) the information and tools necessary for effective planning and response are distributed across the private and public sectors, standard regulatory tools are unlikely to produce security. "Integration of effort, " which involves intensive strategic and operational collaboration between systemically important firms and the government, is a more promising approach .